BPJS Participant Satisfaction Level Evaluation on The Outpatient Installation Pharmaceutical Services RSUD Anuntaloko Parigi - Kusumawati, Afriani; Masyita, Andi Athira; Ambiati, Nurul; Parumpu, Firda Amir; Rumi, Amelia; Dondokambey, Dessy Natalia (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Patient satisfaction is a success metric of a pharmaceutical service. Health insurance like BPJS Health makes it more accessible for patients in need to keep track of their health.Objective: To determine and evaluate the satisfaction level of BPJS participants with pharmaceutical services at the outpatient installation of Anuntaloko Parigi HospitalMethods: Quantitative descriptive research (non-experimental) with 200 respondents as samples. The sampling technique used is purposive sampling with a questionnaire. The processed data were analyzed using the ServQual gap, Customer Satisfaction Index (CSI), and Importance and Performance Analysis (IPA) methodsResults: The gaps for each dimension are: reliability -0.41, responsiveness -0.40, assurance -0.28, empathy -0.40, and tangible -0.61 in the quite satisfied category. The satisfaction level using the CSI measurement method is also included in the quite satisfied category with a CSI value of 78.48%.Conclusion: the satisfaction level of outpatient BPJS participants at Anuntaloko Parigi Hospital is in the quite satisfied category with two service attributes to improve, which are reliability and responsiveness related to the friendliness and the response of officers in serving patients